ANALISIS KELAYAKAN USAHA AGROINDUSTRI PENGGILINGAN PADI KLIBUR, PUTRA HOMA, DAN TEDE SAJA DI DESA HOMA KECAMATAN ADONARA BARAT KABUPATEN FLORES TIMUR - Maria Katarina Bunga Tukan; Marthen Robinson Pellokila; Lika Bernadina (Yayasan Panca Bakti Wiyata Pangandaran, 2026)
This study aims to: (1) determine the operational costs of the Klibur, Putra Homa, and Tede Saja rice milling businesses; (2) analyze business income; and (3) assess business feasibility based on financial and non-financial aspects, using a case study method. The study population consisted of three rice milling business owners and 30 farmers utilizing the milling services, selected purposively. Data were analyzed using cost and income analysis, Net Present Value (NPV), Internal Rate of Return (IRR), Revenue-Cost Ratio (R/C Ratio), and Break-Even Point (BEP), alongside an analysis of non-financial aspects—covering service, social, environmental, and technical factors using a Likert scale. The results indicate that operational costs for the 2023–2025 period were Rp43,074,750 for Klibur, Rp34,295,963 for Putra Homa, and Rp29,996,133 for Tede Saja. Total income earned amounted to Rp39,180,850, Rp35,715,473, and Rp25,796,787, with total revenues of Rp82,255,600, Rp70,011,400, and Rp55,792,900, respectively. Financial analysis shows that all three businesses are feasible to operate, as evidenced by positive NPV values, IRR values ​​exceeding the 12% interest rate, and R/C Ratios greater than 1. The obtained IRR values ​​were 32% (Klibur), 29% (Putra Homa), and 26% (Tede Saja). Regarding non-financial aspects, the rice milling businesses fall into the